On the Interaction between Small Decay, Agent Heterogeneity and Diameter of Minimal Strict Nash Networks in Two-way Flow Model: A Note - Banchongsan Charoensook (Fondazione Eni Enrico Mattei (FEEM), 2019)
In this note, I study the roles of value heterogeneity - i.e., agents are heterogeneous in terms of values of nonrival information thay they possessed - in determining the shapes of two-way flow Strict Nash networks when small amount of decay is present. I do so by extending the two-way flow network with small decay of De Jaegher and Kamphorst (J ECON BEHAV ORGAN, 2015). Results of this extension shows that the effects of value heterogeneity on Strict Nash networks, when small decay is present, largely resemble the effects of heterogeneity in link formation cost - without decay - found in the literature. Another surprising finding is that value heterogeneity can extend the diameters of Strict Nash networks without changing any other properties. In the discussion section of this note, I relate this finding to two well-known concepts in the studies of social networks - small world and preferential attachment.
Keywords: C72; D85; 330; Network Formation; Strict Nash Network; Two-way Flow Network; Branching Network